2018
DOI: 10.1016/j.gaitpost.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between walking speed, T-score and age with gait parameters in older post-menopausal women with low bone mineral density

Abstract: Speed alone explained most of the variance in the gait parameters, while speed and T-score combined increased the explanatory power of the regression models for some of the knee joint variables. Our findings demonstrated that older post-menopausal women, with a broad range of T-scores, are able to walk at comfortably fast speeds, generating gait patterns similar to those of younger women. The results also suggest that strengthening the hip abductor, knee extensor and flexor muscle groups may benefit the gait p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Although the base of gait can predict falls, correcting the walk habitat may be challenging in the elderly. The selection of proper footwear may assist the elderly in achieving better gait stability [30,31]. Footwear plays an essential role in postural and dynamic instability by facilitating somatosensory feedback to the foot [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Although the base of gait can predict falls, correcting the walk habitat may be challenging in the elderly. The selection of proper footwear may assist the elderly in achieving better gait stability [30,31]. Footwear plays an essential role in postural and dynamic instability by facilitating somatosensory feedback to the foot [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 displays the ROCs of gait variables associated with BMD as demonstrated in this study (LI), and walking speed and cadence, which have previously been shown to be a potential parameter associated with low BMD [4,13]. The ROCs of LI, cadence, and walk speed in predicting low BMD were significantly associated with LI [AUC (area under the curve) of 0.75±0.10 (mean ± standard error), 95% confidence interval (CI): 0.55–0.95; P =0.031], but not with cadence (AUC of 0.70±0.10, CI: 0.50–0.91, P =0.080) or walking speed (AUC=0.5±0.11, CI: 0.27–0.73, P ≥0.05).…”
Section: Resultsmentioning
confidence: 99%
“…During the course of aging, postmenopausal women are more susceptible to osteoporosis due to related hypoestrogenism [2]. Such elderly women tend to show reductions in muscle mass and strength, which may affect gait patterns [3,4]. A recent kinetic study demonstrated decreased external hip extension and adduction moments, power generation at the hip and ankle, or hip and knee in postmenopausal women with low BMD compared to normal BMD subjects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our results regarding gait speed were similar to those stated by Lindsey et al [37], who reported an association between gait speed and bone mineral density (BMD). Dostanpor et al [38] also suggested that gait speed was associated with low BMD or aging. This association implies that BMD management can also be an important factor in the rehabilitation process of patients with hip fracture.…”
Section: Discussionmentioning
confidence: 99%